2009
DOI: 10.1370/afm.942
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative Incidence of False-Positive Results in Repeated, Multimodal Cancer Screening

Abstract: PURPOSE Multiple cancer screening tests have been advocated for the general population; however, clinicians and patients are not always well-informed of screening burdens. We sought to determine the cumulative risk of a false-positive screening result and the resulting risk of a diagnostic procedure for an individual participating in a multimodal cancer screening program.METHODS Data were analyzed from the intervention arm of the ongoing Prostate, Lung, Colorectal, and Ovarian (PLCO) Cancer Screening Trial, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
88
0
5

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(94 citation statements)
references
References 35 publications
1
88
0
5
Order By: Relevance
“…A better knowledge of the population regarding the inclusion criteria for CRC screening could contribute to decrease the overall false-positive rate in the following rounds. On the other hand, the risk of obtaining a false-positive result increased with successive screening participation [15,16,26]. This finding is consistent with those from other cancer screening programs.…”
Section: Ongoing Screeningsupporting
confidence: 87%
See 1 more Smart Citation
“…A better knowledge of the population regarding the inclusion criteria for CRC screening could contribute to decrease the overall false-positive rate in the following rounds. On the other hand, the risk of obtaining a false-positive result increased with successive screening participation [15,16,26]. This finding is consistent with those from other cancer screening programs.…”
Section: Ongoing Screeningsupporting
confidence: 87%
“…In addition, more accurate information could be provided to participating individuals. To date, only a few studies have evaluated false-positive results within a CRC screening program [14][15][16]102] and several questions remain unanswered, such as the risk factors associated with a false-positive test or the long-term impact of having a false-positive result. However, we should first agree on the definition of a false-positive result.…”
Section: Editorialmentioning
confidence: 99%
“…Cumulative rates of FP results in repeated screening for several screening modalities were recently reported from the PLCO trial (Croswell et al, 2009). The authors showed a risk of 10.4% for at least one FP result in annual PSA screening during the 3-year screening period.…”
Section: Discussionmentioning
confidence: 91%
“…9 A large number of such procedures will lead to a small number of serious adverse consequences, such as serious infection, induced cardiovascular event, or even anaphylaxis or death. Considering the imprecise estimates of both benefits and harms, and factoring patient values, it seems reasonable that some well-informed health-conscious rational adults might choose to not screen.…”
mentioning
confidence: 99%